2019
DOI: 10.1080/07391102.2019.1704877
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of the effects of sequence variations between HIV-1 and HIV-2 proteases on their three-dimensional structures

Abstract: HIV protease inhibitors (PIs) approved by the FDA (US Food and Drug Administration) are a major class of antiretroviral. HIV-2 protease (PR2) is naturally resistant to most of them as PIs were designed for HIV-1 protease (PR1). In this study, we explored the impact of amino-acid substitutions between PR1 and PR2 on the structure of protease (PR) by comparing the structural variability of 13 PR regions using 24 PR1 and PR2 structures complexed with diverse ligands. Our analyses confirmed structural rigidity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 57 publications
(78 reference statements)
1
8
0
Order By: Relevance
“…One possible explanation for the observed structural asymmetry that we did not consider in this study is the error or packing in the crystallographic structure. We previously showed that 24 positions were involved in crystal packing in the PR2 structure complexed with DRV (PDB code 3EBZ) [37]. In addition, we previously highlighted some structural asymmetry linked to crystal packing in unbound PR2, for example, at positions 3 and 18 [33].…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…One possible explanation for the observed structural asymmetry that we did not consider in this study is the error or packing in the crystallographic structure. We previously showed that 24 positions were involved in crystal packing in the PR2 structure complexed with DRV (PDB code 3EBZ) [37]. In addition, we previously highlighted some structural asymmetry linked to crystal packing in unbound PR2, for example, at positions 3 and 18 [33].…”
Section: Discussionmentioning
confidence: 95%
“…To explore the structural effects of the studied drug resistance mutations, we compared the structural asymmetry in the three 3EBZ mini structures and the 150 modeled mutant structures using an approach based on a structural alphabet [31]. [32,37,38]. Each PR2 region is colored as follows: the Nter and Cter regions in grey, the R1 region in dark blue, the fulcrum region in green, the catalytic region in purple, the R2 region in orange, the elbow region in blue, the flap region in magenta, the cantilever region in yellow, the R3 region in pink, the wall region in cyan, the R4 region in brown, and the α-helix region in red.…”
Section: Detection Of Structural Asymmetry In the Wild-type And Mutanmentioning
confidence: 99%
See 1 more Smart Citation
“…To do so, we computed the RMSD of the 13 structural and functional regions between their two chains (RMSD reg AB ). This criterion has been previously used to compare the local conformations of PR1 and PR2 [28]. Our results showed that the global asymmetry of PR2 is not explained by deformations of only one region, but it is linked to the deformation of several regions.…”
Section: Discussionmentioning
confidence: 68%
“…Figure 1. The 3D structure of PR2 colored according to the 13 regions: the nter region (1-4) is colored in forest green, the r1 region (5)(6)(7)(8)(9) in blue, the fulcrum region (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23) in green, the catalytic-site region (24)(25)(26)(27)(28)(29)(30) in purple, the r2 region (31)(32)(33)(34)(35)(36) in marine blue, the elbow region (37)(38)(39)(40)(41)(42) in magenta, the flap region (43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)...…”
Section: Introductionmentioning
confidence: 99%